Research on spousal violence: Toward a balanced and rigorous approach - Vílchez-Román, Carlos (2016)
AJPH has published a study on intimate partner violence (IPV) that examined the relationship between IPV and community-level factors in post-Soviet countries.1 The author used survey data from a study conducted between 2005 and 2012 in five counties and applied a logistic multilevel modeling to identify the contextual factors associated with IPV. Although the procedure and statistical analysis is detailed and makes possible a replication of the study, this letter discusses the theoretical approach used to analyze IPV.